Parent, partner and individual contexts of very early first sex experiences among young men and their links to subsequent reproductive health outcomes. Issue 12 (22nd November 2021) - Offiong, Asari; Lindberg, Laura; Jennings, Jacky M.; Dittus, Patricia J.; Marcell, Arik V.
Abstract: Research indicates that upwards to 30% of US urban Black male adolescents report first sex younger than age 13; however, there is limited literature on the sexual and reproductive health outcomes and contexts of these early first sex experiences. This exploratory study described sexual and reproductive health histories and explored personal, partner and parent contextual factors associated with first sex experiences occurring at 13 years or younger among a sample of US urban young men aged 15–24. Participants were assessed on their demographics and sexual health histories and a subset of young men were assessed on the contextual factors related to their first sex experience. Pearson chi-squared tests examined factors associated with early first sex and Fisher's exact tests examined associated contextual factors. First sex at 13 years or younger was reported by 29% of young men. A higher proportion of young men who had first sex at 13 or younger than those who had sex onset at 14 or older reported having got someone pregnant, having a "much older" first partner, and relationship satisfaction with their mother (16%) and father (12%). Study findings highlight the need to better understand urban young men's early first sex experiences, including the support needed to promote their healthy sexual development.